3-amino-5-(piperidin-1-yl)thiophene-2,4-dicarbonitrile - Al-Adiwish, Wedad M.; Adan, Dalina; Mohamed Tahir, Mohamed Ibrahim; Wan Ahmad, Wan Yaacob; Kassim, Mohammad (International Union of Crystallography, 2012)
In the title compound, C11H12N4S, the thiophene ring is roughly planar, with a maximum deviation of 0.012 (1) Å for the S atom, and makes a dihedral angle of 7.89 (8)° with the mean plane of the piperidine ring, which is in a chair conformation. The crystal packing is stabilized by pairs of centrosymmetric intermolecular N—H(...)N hydrogen bonds, which results in the formation of a step-wise chain parallel to [10An].